Scientific Evaluation of Dhuma Yoga (An Ayurvedic Fumigation Medicine) as Preventive and Curative on Symptoms of Covid-19 Disease - Siva Ram, (International Journal of Ayurveda and Pharma Research, 2021)
Covid-19, an infectious disease caused by a novel coronavirus SARS-CoV-2 spreads primarily through droplets of saliva or discharge from the nose when an infected person talks, coughs or sneezes where the viruses are active in the environment within the suspended micro droplets. Sanitization of environment to weaken/terminate the virus and halting the replication of virus inside the host along with symptomatic treatment is the primary approach to end the pandemic. In Ayurveda, Dhupana (medicated fumigation of vicinity) and Dhumapana (medicated smoking) therapies done by drugs of herbal/animal/mineral origin are a swift way to decontaminate the environment and Respiratory system. Dhuma (medicated fumes) is a unique drug delivery system acting directly on respiratory tissues which can deliver quick results in this Covid-19 pandemic by its local and systematic effects recommended by AYUSH ministry in the guidelines for Covid-19. We intend to put forward the scientific explanation of powerful Ayurvedic Cannabis based polyherbal dhumapana (medicated smoking) medication named Dhuma Yoga available in the market as an alternate remedy for Covid-19 whose four out of five herbal ingredients are in the list of WHO manual of traditional medicine. We emphasized on Vijaya (Cannabis sativa Linn.) as the centre of formulation because it is a Rasayana (rejuvenative) herb having Vyavayi (fast acting) and Yogavahi (synergetic) properties. Phytochemicals of all the herbal ingredients of Dhuma Yoga formulation are studied through in silico, In vitro and In vivo studies for Covid-19 with favourable outcomes.